Technological Adoption in the Philippine Advertising Industry - Zamora, Elvira A.; Lingan, Eloisa H. (Philippine Management Review; Vol 7 (1997), 2016)
This study was conducted in order to determine how technology for the production of television advertisements is adopted in the Philippine advertising industry.  An analysis of the industry structure showed that digital technology acquisition and adoption are more the concerns of commercial production and post-production houses than of advertising agencies, which subcontract most of the work to these advertising suppliers.  A test of two technology adoption models showed that the psychographic model, more than the benefit-cost model, better reflected the decision making process involved in the acquisition and adoption of digital technology.  Results show importance and productivity are the better predictors.  Perceived importance of the new technology is the primary consideration, while factors such as price and effect on quality and productivity appear to play a secondary role.